Research on the Response to Crisis, Inflation, and Economic Development - Li, Yutong (Transactions on Economics, Business and Management Research, 2024)
Around 2008, due to the subprime mortgage crisis and the real estate market crisis, a large number of banks in the United States and even the world went bankrupt. This has led to a sharp rise in the unemployment rate and a sharp decline in the per capita GDP of the United States. As a result, the United States and the global economy fell into a severe recession, which became known as the 2008 financial crisis. Faced with the financial crisis, the US government has adopted different measures and policies. Although these measures did restore economic conditions to some extent, they also had a negative impact on the economic system. This paper will discuss the US financial crisis by analyzing different papers and data (such as US GDP and unemployment rate), and analyze the most suitable policy for the current economic situation by analyzing and comparing the advantages and disadvantages of different policies. By studying fiscal policy and monetary policy, this paper finds that the combination of fiscal policy and monetary policy can achieve better results, and this way of combining the two policies may be better able to deal with the possible financial crisis in the future.